Why Do Drivers Still Go Against Traffic Flow? : A Study of Regulations, Social Responses, and Perspectives from Islamic Political Jurisprudence (Siyasah Fiqh) - Aliffa, Salwa Putri; Sukandi, Ahmad (Jurnal Ilmu Hukum Kyadiren, 2025)
The prevalence of traffic violations, particularly wrong-way driving, in the strategic areas of Bandar Lampung City highlights the limited effectiveness of local regulatory efforts in managing urban traffic behavior. This study aims to assess the implementation of Bandar Lampung Mayor Regulation No. 01 of 2018 and examine it through the lens of fiqh siyasah tanfīdhīyah (Islamic administrative governance). Employing a qualitative approach with a descriptive-analytical method, data were collected through field observations, in-depth interviews, and document analysis. The findings reveal that the enforcement of the regulation remains suboptimal due to inadequate public outreach, weak institutional oversight, and low levels of legal awareness among the public. From the perspective of fiqh siyasah tanfīdhīyah, the policy’s implementation does not fully embody the principles of justice, public welfare (maslahah), and administrative responsiveness. This study underscores the necessity of a collaborative, multi-stakeholder approach involving governmental authorities, community leaders, and road users to foster more effective and equitable traffic governance